Evaluasi Sistem Informasi Manajemen Berbasis Mobile untuk Efisiensi Operasional di Perusahaan Logistik - Ilham Aditya Permana; Angga Putra Al-Farrezs; Daffa Nino Ramadhan; Muhammad Reza Abdillah Syahik; Reza Adha Nugraha (Jurnal Riset Informatika dan Inovasi, 2024)
This research evaluates the impact of mobile-based Management Information Systems (MIS) on enhancing operational efficiency in the logistics companies in Indonesia. Using a qualitative descriptive approach, the study employed semi-structured interviews and direct workplace observations to understand the implementation and effects of mobile SIM. The findings indicate that mobile SIM effectively manages fleet operations, reduces operational costs, enhances shipment transparency, and supports better data analysis. This research contributes significantly improving operational performance within the logistics industry.